Inmigración, Desarrollo y Estrategias de Movilidad Social - Oso Casas, Laura (Revista Española de Desarrollo y Cooperación, 2023)
The remittances don’t always have a positive impact on development. Actually, the institutional view of co-development may be linked to a covered policy of voluntary return and the policies of remittances may have negative impacts not only on migrants, who have to suffer the fact of leaving their country and a tough activity abroad, but also on the country of origin. The author analyses these facts through a study of the Spanish migration during the 60s and 70s.